Probiotics, prebiotics and synbiotics use in neonates : a critical appraisal of the evidence and evaluation of its application by the food industry - Mugambi, Mary Letizia Nkatha (Stellenbosch : Stellenbosch University, 2014)
Thesis (PhD)--Stellenbosch University, 2014.